NAVIGATING LINGUISTIC LANDSCAPES: AN IN-DEPTH ANALYSIS OF MULTILINGUALISM IN CONTEMPORARY SOCIETY - Shakhnoza Sharofova (Scholar Express Journal, 2024)
This article delves into the intricate tapestry of linguistic landscapes, offering an in-depth analysis of multilingualism in contemporary society. We navigate the evolving role of languages in public spaces, exploring their visual representation and unraveling the cultural and social dimensions embedded in linguistic landscapes. Tracing the historical evolution of multilingualism, we examine key events and influences that have shaped linguistic diversity, particularly in the context of globalization. The article scrutinizes the current state of multilingualism globally, dissecting its impact on various domains such as education, business, and technology, while addressing the associated benefits and challenges. Factors influencing linguistic landscapes, including migration, globalization, and urbanization, are scrutinized, along with the role of policies and institutions in managing multilingual environments. Case studies illustrate diverse linguistic landscapes, highlighting urban and rural settings, and showcasing examples of successful language integration. The article navigates the challenges posed by linguistic diversity in communication and education, balancing them against opportunities for cultural enrichment and social cohesion. Furthermore, we examine language preservation and revitalization efforts, shedding light on initiatives to safeguard endangered languages, community-based endeavors, and the intersection of technology in language preservation. Predicting future trends, the article explores the implications for education, policy-making, and cultural understanding. It also considers the evolving role of artificial intelligence and communication technologies in shaping multilingual interactions. This article synthesizes key findings to underscore the significance of navigating linguistic landscapes for fostering global understanding. It provides a comprehensive overview of the complex interplay between languages, cultures, and societies, concluding with potential avenues for further research and exploration in the dynamic realm of multilingualism
Keywords: Linguistic; multilingualism; society; representation